Al-Naz‘ah al-Khārijīyah fī Afkāri wa Ḥarakāti al-Shaykh Ahmad Rifā‘i bi Kālī Sālāk - Sa'ad, Muhlisin (Center for Study of Islam and Society (PPIM) Syarif Hidayatullah State Islamic University, 1995)
Rifa'i is a 'scholar who spent over 20 years old to study in the Middle East, particularly in Mecca and Cairo. Upon returning from the Middle East, Rifa'i settled in Kaliwungi, Kendal, Central Java. There he devote attention to teaching religious sciences as well write the book. He also actively engage students and the general public to raise awareness of the socio-religious people in order to erode the moral crisis is the result of the work of the Dutch colonial behavior. To that end, Ahmad Rifa'i critique of the colonial government and also the traditional feudal aristocracy became agents.DOI: 10.15408/sdi.v2i2.837